Physics I for dummies - Holzner, Steven (For dummies, 2011)
Explains the basic principles of physics in a simple, clear and entertaining fashion. It includes information on many physics topics and is ideal for anyone who wants to review for an exam, is looking for a course supplement, or is simply curious to learn about physics.